The Relationship of Islam and The State in Contemporary Islamic Political Discourse in Indonesia - Sholichuddin, Muhamad Afrizal; Putu Muchtar, Nicky Estu; Ratna, Rizky Dwi (Dirasah International Journal of Islamic Studies, 2023)
The purpose of this study was to relate the views in the context of Islamic politics in Indonesia, this article is intended to explore issues relating to relations between Islam and the state. This study was motivated by the desire to criticize the development and relationship between Islam and the state which is very dynamically coloring the political situation in “Islamic majority country” Indonesia. This article concludes that understanding the relationship between religion and state with an Islamic political approach is not meant to establish a religious state or an Islamic state of Indonesia but rather to fill the spaces that are functionally religion in order society, nation, and state., and secularistic relations.